Pengaruh Media Pembelajaran Berbasis Lectora Inspire terhadap Hasil Belajar Siswa pada Pelajaran Matematika Kelas II SD Negeri 101788 Marindal I T.A. 2024/2025 - Ester Linawati Manurung; Dody F. Pandimun Ambarita; Robenhart Tamba; Faisal Faisal; Husna P. Tambunan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this research is to determine the effect of Lectora Inspire-based learning media on student learning outcomes in Mathematics for 2nd grade students at SD Negeri 101788 Marindal I during the 2024/2025 academic year. This research adopts an experimental study with the True Experimental Design using a Pretest-Posttest Control Group Design. The population consists of all 2nd grade students at SD Negeri 101788 Marindal I, while the sample consisted of Class II A as the experimental group and Class II B as the control group. The research instruments were tested through validity testing, reliability testing, item discrimination analysis, and item difficulty analysis. Data analysis techniques used in this research is the normality test, homogeneity test, and hypothesis testing. The results of the hypothesis test on the pretest and posttest of the experimental class showed that tcount > ttable is 41,223 > 1,713. While the results of the hypothesis test on the pretest and posttest in the control class showed that tcount > ttable is 12,901 > 1,724. These results indicate that Ha is accepted, meaning there is a significant effect of Lectora Inspire-based learning media on student learning outcomes Mathematics for 2nd grade at SD Negeri 101788 Marindal I during the 2024/2025 academic year.